Ensino de ciências por investigação: contribuições da leitura para a alfabetização científica nos anos iniciais - Silva, Tamiris de Almeida (2020)
This text starts from the idea of a Science Teaching that offers students the possibility of using their scientific knowledge in understanding and interacting with the world around them. The research is based on the development of an Investigative Teaching Sequence (SEI), entitled ―How does a rainbow form in the sky?‖, with students of a 5th grade elementary school class from Arapiraca-AL. The objective was to analyze the contributions of reading texts, of the legendary text genre, to the promotion of the Scientific Literacy for a 5th grade elementary school, through the didactic approach of teaching by investigation. To guide the research, we started from the following problem: What are the contributions of reading, of the legendary text genre, in promoting the Scientific Literacy for students on a 5th grade elementary school, through teaching by research? Thus, it was sought at the Qualitative Approach the methodological assumptions that consisted of an application research, using as a data collection instrument the development of the Didactic Sequence, composed of activities with open questions. The results pointed out that reading texts in science teaching allowed the inclusion of students in scientific culture through learning concepts, broadening vocabulary, understanding the nature of science, clarity about the textual legend genre, reading development and of science writing and formation of critical citizens who are aware of their rights and duties in society.